‫الإسلامية‬ ‫الحضارة‬ ‫صياغ‬ ‫في‬ ‫ودورها‬ ‫العربية‬ ‫اللغة‬ - Dihyatun Masqon (Universitas Darussalam Gontor, 2015)
Language is a communication tool that is used by every human being to convey a particular purpose. Every human group has a different language to another. Language differences may occur in intonation, term and writing. Therefore language is very important in human life, even very influential in human civilization. Especially Arabic, Allah has determined that language is the language of revelation in which the truth was taken for granted through the boundaries of space and time. In human civilization, Arabic has a very important history. Arabic is a very old language, which has been used since man was created. Arabic is currently considered important by the world and made one of the languages of the United Nations. Furthermore, the advance of Islamic civilization has been greatly influenced by Arabic. In fact, Western Civilization has been able to develop due attention to the Arabic language. From that perspective, this article attempts to expound the role of Arabic language in the formation of Islamic civilization. In the context of civilization, understanding Arabic and mastering its use, either actively or passively, is a key condition to understanding the beauty and glory of civilization. History has recorded with gold ink, civilization based product revelation of various dimensions, spiritual, intellectual, and emotional. Thus, the duty of Muslims as perpetrators and manufacturer of Islamic civilization is to carefully read and explain continuously the great Islamic civilization.